Concentration and Distribution Characteristics of Airborne Fungi in the Ambient Air of Milad Hospital, Blood Transfusion Organization and Tehran's Shahrake Ghods Wastewater Treatment Plant - farshad bahrami asl; mahdi farzadkia; kazem naddafi; darush zeynalzadeh; anahita dehghani (Mazandaran University of Medical Sciences, 2015)
Background and aims: Recently contact with bioaerosols has been presented as an important problem which endangers human being’s health. The aim of this investigation is to compare potential of separation of fungal aerosols in the air around Tehran’s Milad hospital, blood transfusion organization and waste water treatment plant of Tehran’s Shahrake Ghods. methods: this cross-sectional investigation was done in Milad hospital, blood transfusion organization and Tehran’s Shahrake Ghods waste water treatment plant within for 4 months. The sampling was done passively for 1 hour and once in 6 days. The culture medium was Sabouraud dextrose agar. Results: comparing selected sampling stations the most fungal density was for 100 meters after the last unit of waste water treatment plant (67 CFU) and the least density was for Milad hospital (30 CFU). Dominant genera of fungal in waste water treatment plant and blood transfusion organization was related to Cladosporium (in order of 49% and 84%) and in air around Milad hospital was related to Alternaria (47%). Conclusion: according to the results processing and operating sections in waste water treatment plant can be effective in fungal density and separation of bioaerosols. Therefore it seems to be vital that the responsible organizations should do necessary actions to develop guidelines and standards related to bioaerosols. Also appropriate administration of environmental health in waste water treatment plant can be an important factor in reduction of aerosol separation.